The Role of Teacher Interpersonal Communication on the Development of Social Skills of Autism Spectrum Disorder (ASD) Students - Azizah, Berlianti Apriliana Nur; Novianti, Ranti; Ummah, Umi Safiul (Proceedings Series of Educational Studies, 2024)
Autism Spectrum Disorder (ASD) is a developmental disorder in childhood, marked by delays in cognition, language, behavior, communication, and social interaction. This study aims to explore how teacher-student interpersonal communication influences the skill development of ASD students. Using a qualitative case study approach, direct observation, and in-depth interviews were conducted with three classroom teachers, the principal, and four ASD students. The findings reveal that teachers' interpersonal communication significantly impacts the social skill development of ASD students. By fostering openness and equality, teachers build trust and emotional bonds, enhance students' social skills, learning focus, and emotional stability, and employ appropriate teaching methods. Teachers integrate positive behaviors through routines like greeting peers or teachers and provide concrete examples and repeated explanations to develop peer relation skills. Empathy from teachers allows adaptive learning tailored to students' needs, using visual aids to aid comprehension. Supportive attitudes and creative teaching methods foster a strong task orientation and academic ability in ASD students. Consistent routines, such as the salim culture, help students understand and follow school rules, promoting positive behavior. Future research should further evaluate the effectiveness of these strategies and programs and explore additional factors influencing ASD students' learning success. Keywords: Teacher Interpersonal Communication; Autism Spectrum Disorder (ASD); Social Skills